Lymphatic malformation of major epiplon with inflammatory acute abdomen clinic in a teen patient: case report (Horizontes de Enfermería, 2019)
Background: Abdominal lymphatic malformations are benign but very rare findings. They usually look like as lymphatic dilatation, especially in male children. There are very few cases reported in which this malformation appears in peritoneal cavity and retroperitoneal space, being the mesentery of the small intestine the most common followed by the peritoneum.  Case Presentation: We are the first to describe an Ecuadorian case of abdominal lymphatic malformation in a 12.5-year-old teenager with acute abdomen. One year later the patient has not reported recurrencesn. Conclusions: In the presence of acute abdomen, we cannot ignore this pathology. We highlight ultrasound as a diagnostic and follow-up method. Complete surgical resection is curative.
Keywords: lymphatic malformation; acute abdomen; lymphangioma; peritoneum